Dịch chuyển vỏ Trái Đất theo số liệu GPS liên tục tại Việt Nam và khu vực Đông Nam Á - Minh, Lê Huy; Feigl, Kurt; Masson, Frédéric; Công, Dương Chí; Bourdillon, Alain; Duchesne, Patrick Lassudrie; Thắng, Nguyễn Chiến; Thành, Nguyễn Hà; Nam, Trần Ngọc; Lan, Hoàng Thái (Vietnam Journal of Earth Sciences, 2012)
SUMMARYCrustal motion from the continuous GPS data in Vietnam and in the Southeast Asian regionThis paper presents an estimation of the velocity of the Earth’s crust in Vietnam and the Southeast Asian region, determined from the GPS data in nearly 5 years (4/2005-12/2009) at 3 sites in Vietnam (Hanoi, Hue and Ho Chi Minh city) plus more than 20 ones in Southeast Asia and other regions using GAMIT software. The horizontal velocity vectors in ITRF2005 at the considered Southeast Asian stations show that they drive to the south-eastward, but the KUNM, Hanoi and Hue (with velocity of about 32-35mm/yr) move faster than the Ho Chi Minh city, NTUS and BAKO (with the velocity of 22-26mm/yr) ; meanwhile the PIMO drives to the northwest with the velocity of 30 mm/yr. The fact that relative velocity vectors with respect to the Eurasian plate decrease from 9.7 mm/yr at Hanoi, 6.9 mm/yr at Hue to 4.0 mm/yr at Ho Chi Minh city, as well as the increase of the motion azimuthsfrom 139°8 at Hanoi to 226°3 at HCM city show that the Indochina block rotates clockwise ; however, its northern part moves faster than the southern one. The increase of the azimuths of the relative velocities with respect to the Sundaland block from 201°6 at Hanoi, 221°3 at Hue to 254°4 at Ho Chi Minh City also implicates the clockwise rotation of the Indochina block. Significant differencesof the relative velocities with respect to Sundaland at the stations in this block (1.4 mm/yr at BAKO, ~12 mm/yr at NTUS and HCM city, and 7.8 mm/yr at Hue) implicate that the Sundaland also undergoes asignificant internal deformation.